The Effect of Implementing a Project to Strengthen the Profile of Pancasila Students by using a Problem-Based Learning Model in Improving Student Learning Outcomes at the National Junior High School in Malang - Pawolung, Yumiati Reni; Andayani, Endah; Naim, Naim (International Journal of Business, Law, and Education, 2025)
This study aims to determine the improvement of students' academic performance through the implementation of Pancasila Student Profile Development Programme using problem-based learning models with the concept of local knowledge. Class VII of SMP Nasional Malang in Sukun, Bandungrejosari, Malang for the year 2024. An experimental approach was adopted in this study using a quasi-experimental design. An unbalanced group pretest-post-test design was used as the quasi-experimental design. The sample of the study was Grade VII students of SMP Nasional School in Malang. The school has two classes; Class VII D is the experimental class with 33 students while Class VII A is the control class with 33 students. Descriptive statistical and inferential analysis are used in the data analysis. The findings show that the implementation of the Pancasila Student Profile Development Program using the problem-based learning model is highly effective in improving students' learning outcomes in terms of local intelligence